The competency of the novel through‐the‐scope suture device for gastric mucosal defects: In vivo study in a porcine model (with video) - Mamoru Ito; Akira Dobashi; Takanori Tominaga; Toshiki Futakuchi; Naoto Tamai; Machi Suka; Kazuki Sumiyama (DEN Open)
Abstract Objectives Endoscopic closures of mucosal defects following endoscopic resection can be challenging and time‐consuming. The novel through‐the‐scope suture device has demonstrated acceptable closure times, but its learning curve is still unknown. This study aims to evaluate the number of cases required to achieve competency in this device. Methods Two endoscopists participated; a novice with less than 400 experiences in upper gastrointestinal endoscopy and an expert with over 500 experiences in endoscopic submucosal dissection. Neither endoscopist had previous exposure to the device. In four porcine models, 24 gastric mucosal defects, each 2–4 cm in diameter, were created by endoscopic mucosal resection with ligation. Each endoscopist performed endoscopic closure for 12 mucosal defects with a single through‐the‐scope suture device per lesion. The primary endpoint was the number of cases needed to reach competency, defined as achieving a procedure time below the average closure time reported in the literature. Secondary endpoints included procedure time, complete closure success rates, and incidence of adverse events. Results The mean defect size was 2.9 (±0.2) cm. Competency was achieved after six cases in the expert and seven cases in the novice. The median closure time was 9.0 (interquartile range [IQR]: 6.0–11.0) min for the expert and 8.0 (IQR: 6.2–9.7) min for the novice (p = 0.862). Complete closure success rates were 75.0% (n = 9) for the expert and 83.3% (n = 10) for the novice. No adverse events were reported. Conclusions A small number of cases were required for both expert and novice endoscopists to reach competency in the novel through‐the‐scope suture device.